Examination of physical activity and life quality levels of university students based on the analysis of the WHOQOL-BREF indicators - Bakhytzhan Omarov; Baglan Yermakhanov; Almira Ayapbergenova; Anuarbek Amanov; Aigul Turayeva; Talgat Daniyarov (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study investigates the impact of physical activity on the quality of life among university students using the WHOQOL-BREF questionnaire, focusing on three primary dimensions: physical health, psychological health, and social relations. Sixty students were divided into two groups based on their lifestyle patterns: thirty engaged regularly in sports and physical activities (Group A), and thirty led a predominantly sedentary lifestyle (Group B). The results highlighted significant positive correlations between regular physical activity and both physical and psychological health. Specifically, Group A exhibited superior physical and psychological health scores compared to Group B, substantiating the hypothesis that physical activity significantly enhances these aspects of quality of life. Conversely, no significant difference was found in social relations between the two groups, suggesting that the influence of physical activity on social interactions might be less straightforward and possibly moderated by other unmeasured variables. These findings underscore the necessity for universities to foster environments that encourage physical activities, as part of a broader strategy to enhance overall student well-being and academic performance. The study contributes to the existing literature by reaffirming the multifaceted benefits of physical activity and calls for integrated health promotion strategies within educational institutions to support the holistic development of students.